2018
DOI: 10.1080/02770903.2018.1493599
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring in asthma control: a randomized controlled trial

Abstract: The developed program for home monitoring of patients with asthma was applicable and offered the patients support in managing their disease. Further studies with more selected patients are needed to confirm its usefulness in improving asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Our findings show that the AioCare V R system can be recommended for selfmonitoring, because nearly all patients reported their symptoms daily in the smartphone application. Moreover, the AioCare V R system enables tele-monitoring, which offers further support to patients with asthma (14). Making AioCare V R data available to the physician, via tele-monitoring, can improve patient adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that the AioCare V R system can be recommended for selfmonitoring, because nearly all patients reported their symptoms daily in the smartphone application. Moreover, the AioCare V R system enables tele-monitoring, which offers further support to patients with asthma (14). Making AioCare V R data available to the physician, via tele-monitoring, can improve patient adherence.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, no difference in asthma control test (ACT) was found in a similar study, including one group of adults reporting PEF and ACT by SMS and thereafter receiving a response on the reported values, compared to a group not reporting results by SMS or receiving such feedback. 16 A systematic review concluded that health care through cell phones using standard care with reminders, disease monitoring and management and education through cell phone voice and SMS, can help improve health outcomes and care processes for various clinical areas. 6…”
Section: Discussionmentioning
confidence: 99%
“…Asthma studies: the mean ages of the patients were 49 [40] and 50 years [41]; however, the age range in a study by Kim et al [41] was broad (19-72 years). Approximately onethird [41] to half [40] of the study populations were male. The studies included patients with either moderate-to-severe [40] or fragile [41] asthma.…”
Section: Patient Characteristicsmentioning
confidence: 96%
“…Approximately onethird [41] to half [40] of the study populations were male. The studies included patients with either moderate-to-severe [40] or fragile [41] asthma. In the former, this meant that patients were eligible if they had at least one asthma exacerbation in the past year that required an intensification of inhaled corticosteroid therapy.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation